In silico and Genetic Analyses of Cyclic Lipopeptide Synthetic Gene Clusters in Pseudomonas sp. 11K1 - Zhao, Hui; Liu, Yan-Ping; Zhang, Li-Qun (Frontiers in Microbiology, 2019)
Pseudomonas sp. 11K1, originally isolated from rhizosphere, possesses inhibitory activity against plant pathogenic fungi and bacteria. Herein, the genome of strain 11K1 was sequenced and subjected to in silico, mutational, and functional analyses. The 11K1 genome is 6,704,877 bp in length, and genome mining identified three potential cyclic lipopeptide (CLP) biosynthetic clusters, subsequently named brasmycin, braspeptin, and brasamide. Insertional and deletion mutants displayed impaired brasmycin and braspeptin production, and lost antifungal activity, but retained antibacterial activity against Xanthomonas oryzae. The structures of these two active CLPs were predicted based on adenylation (A) domains. Brasmycin is composed of nine amino acids and belongs to the syringomycin class, while braspeptin is a 22 amino acid cyclic peptide belonging to the tolaasin group. Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) mass spectrometry analysis revealed that brasmycin and braspeptin have different molecular weights compared with known syringomycin and tolaasin members, respectively. Mutation of brasmycin and braspeptin gene clusters affected both biofilm formation and colony morphology. Collectively, these results indicate that Pseudomonas sp. 11K1 produces two novel CLPs that may help bacteria compete for nutrients and niches in the environment.